Daya Dukung Perikanan Alami di Waduk Gondang Kabupaten Lamongan - Fuquh Rahmat Saleh; Agung Pamuji Rahayu (Jurnal Sumberdaya Akuatik Indopasifik, 2018)
The Gondang Reservoir is the largest in the Lamongan District, another function this reservoir for irrigation is also for use fishery and tourism. Fisheries production in this reservoir are not optimal and number of tourist getting lower, that result public welfare has not yet create. Therefore we required the data about carrying capacity natural fisheries Gondang reservoir for development of optimal and sustainable water management. This research used the descriptive method with purposive sampling at May until August 2018. Analysis carrying capacity use approach result the water primer productivity with Beveridge Index. Average result of water primer productivity in Gondang Reservoir was 86,26 gC/m2/year. Carrying capacity natural fisheries in Gondang reservoir is 4,4 tons of fish/year or 12,17 kg of fish/year.